Lamps and Lighting Devices in Late Antique Funerary Liturgies of the Levantine Provinces of the Later Roman Empire - Bollók, Ádám; Dayan, Ayelet (2023)
Pottery lamps are frequent occurrences in late antique Levantine mortuary assemblages. This holds particularly true for communal tombs, in which their numbers can sometimes reach up to a few hundred pieces in a single burial space. The present paper distinguishes four major locations where lamps were generally deposited in these mortuary contexts: 1) the outer entrance areas of tombs, including the steps descending to tomb doors, 2) small niches carved into the outer or inner walls of tombs, 3) the immediate proximity of the deceased buried in the loculi or burial troughs of the tombs, including the separating walls and covering slabs of troughs, 4) and the tomb’s central chambers. Based on a database gathered for and presented in the present study, it is argued that while Location 1 lamps were definitely deposited with a commemorative intent, most probably mainly by later visitors to the tombs, Location 2 to 4 lamps reflect a wide array of practical and ritual considerations, from illuminating the dark inner spaces of tombs to providing apotropaic protection for the departed. On the strength of a brief survey of other regions of the Eastern Mediterranean, it is further argued that Location 4 lamp deposits with several dozens to a few hundred lamps attest to a specifically Levantine practice, which can be associated with Christian burial communities. The last section of this paper therefore reviews several early Christian texts to show that church authorities disagreed with the use of artificial light in funerary contexts in given periods and in certain cult settings only, while early Christian light symbolism provided fertile ground for using artificial light and lighting devices in ordinary mortuary contexts.